Strategic Innovation and Economic Growth - Allen C. Head; Beverly J. Lapham (Queen's University, Department of Economics, 1990)
Strategic interaction among oligopolistic innovators and its implications for economic growth are examined in two dynamic computable general equilibrium models. In each environment, technologies for producing a final good are such that the profits of any intermediate good producer depend on the quality of all intermediate goods. This leads to strategic innovation choices which affect equilibrium growth rates. In the first economy, these spillovers lead to long-run output growth rates which fluctuate around a constant level. This level is affected by the degree of spillovers, the length of firms' planning horizons, the number of firms, and average innovation costs. In this economy a firm unequivocally benefits from innovation by other firms. A second economy is also considered in which innovation by other firms may harm intermediate goods producers. This results as innovation leads to rising factor costs. This second economy also exhibits continual output growth but at a decreasing rate. The economy can easily be modified to exhibit long-run growth rates which fluctuate about a constant. We consider two examples: population growth at a constant rate and intermediate goods' technologies affected by average quality.
Keywords: 330